10.1002/9781118797914 (CrossRef Listing of Deleted DOIs, 2000)
BACKGROUND: Infestation of canines with ectoparasites is a significant concern worldwide in both medical and veterinary fields, especially in Iran, due to the transmission of pathogenic agents. OBJECTIVES: This study aimed to assess the prevalence and diversity of ectoparasites found in dogs in Isfahan County. METHODS: A total of 138 dogs-comprising 57 stray dogs, 38 herd dogs and 43 owned dogs-were randomly selected and examined between July 2023 and July 2024. The body surfaces of the dogs were inspected for ectoparasites, including ticks, mites, lice and fleas. These parasites were directly removed from the skin of the examined dogs for identification. RESULTS: Results showed that among the 138 dogs examined, 54 (39.13%) hosted external parasites. Of these, 26 (48.14%) were affected by ticks, 15 (27.77%) by mites, 9 (16.66%) by fleas and 4(7.40%) by lice. A significant difference in prevalence was observed based on the sex and age of the dogs (p < 0.05). The highest incidence of external parasite infestation occurred during the spring season. CONCLUSIONS: These findings indicate a notable prevalence of ectoparasites among dogs in Isfahan County. Given the known zoonotic potential of several identified species, these results highlight the need for further studies on pathogen transmission and strengthened veterinary and public health measures.